Noncoherent adaptive channel identification algorithms for noncoherent sequence estimation. - Schober, R.
In this letter, two novel noncoherent adaptive algorithms for channel identification are introduced. The proposed noncoherent least-mean-square (LMS) and noncoherent recursive least squares (RLS) algorithms can be combined easily with noncoherent sequence estimation (NSE) for M-ary differential phase-shift keying signals transmitted over intersymbol interference (ISI) channels. It is shown that the resulting adaptive noncoherent receivers are very robust against carrier phase variations. For zero frequency offset, the convergence speed and the steady-state error of the noncoherent adaptive algorithms are similar to those of conventional LMS and RLS algorithms. However, the conventional algorithms diverge even for relatively small frequency offsets, whereas the proposed noncoherent algorithms converge for relatively large frequency offsets. Simulations confirm the good performance of NSE combined with noncoherent adaptive channel estimation in time-variant (fading) ISI channels
Keywords: ISI channel; M-ary differential phase-shift keying signals; Adaptive noncoherent receivers; Carrier phase variations; Convergence speed; Frequency offsets; Intersymbol interference channels; Noncoherent adaptive channel identification algorithms; Noncoherent least-mean-square.; Noncoherent recursive least squares; Noncoherent sequence estimation; Steady-state error; Zero frequency offset